2004
DOI: 10.1007/s11095-004-7685-3
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Basic Drugs with Lipid Bilayers Using Liposome Electrokinetic Chromatography

Abstract: These studies demonstrate the overall buffer ionic strength at a given pH is more important than buffer type and concentration. The interaction of positively charged drugs with charged lipid bilayer membranes is selectively influenced by the pKa of the drug. Liposomes are more biologically relevant in vitro models for cell membranes than octanol, and LEKC provides a unique combination of advantages for rapid screening of drug-membrane interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
39
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 42 publications
1
39
0
Order By: Relevance
“…The bilayer structure of vesicles resembles that of cell membranes, and although many components of the latter such as peripheral and integral membrane proteins, ionchannels, etc., are typically not included by design in vesicle PSPs for a variety of reasons (increased cost, complexity, lack of commercial availability), both surfactant-and phospholipid-based vesicles have nevertheless proven to be useful for modeling a number of biological and nonbiological processes [50][51][52][53] including the prediction/estimation of drug absorption [54], blood-brain barrier penetration [55], intestinal permeability [56], drug interactions with lipid bilayers [53,57,58], protein-liposome interactions [59], octanolwater partitioning [45,60,61], etc.…”
Section: Introductionmentioning
confidence: 99%
“…The bilayer structure of vesicles resembles that of cell membranes, and although many components of the latter such as peripheral and integral membrane proteins, ionchannels, etc., are typically not included by design in vesicle PSPs for a variety of reasons (increased cost, complexity, lack of commercial availability), both surfactant-and phospholipid-based vesicles have nevertheless proven to be useful for modeling a number of biological and nonbiological processes [50][51][52][53] including the prediction/estimation of drug absorption [54], blood-brain barrier penetration [55], intestinal permeability [56], drug interactions with lipid bilayers [53,57,58], protein-liposome interactions [59], octanolwater partitioning [45,60,61], etc.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, they can be analyzed by CE, and they proved useful as anionic pseudostationary phases in EKC ( ; for recent reviews see [23,24]. It was found that, besides the pH, the kind of the electrolytes [6,25] and its ionic strength [5,18], and the preparation procedure of the vesicles influences the electrophoretic properties of the particles [23,26]. If their electrophoretic mobility is affected upon attachment of ligands, this change can be used to assess, or even quantify, the interaction in a form of ACE.…”
Section: Introductionmentioning
confidence: 99%
“…Also, CE has been used to assess liposomal drug delivery systems in a few cases [18][19][20][21][22]. Liposomes have, however, primarily been introduced into capillaries in studies directed at estimating drug lipophilicity in relation to membrane permeability properties [2][3][4][5][23][24][25][26][27][28]. These studies have been conducted using the liposomes as a pseudostationary phase, i.e., by EKC [2-5, 23-26, 28] or by CEC [27].…”
mentioning
confidence: 99%
“…The differences observed between the two lipophilicity estimates at pH 7.4 may at least to some extent be ascribed to electrostatic interactions between the partly charged compounds and the net negatively charged liposomal phase, which are not present in the octanol-water system. Biological membranes are negatively charged and, thus, liposomes with lipid compositions like the one employed in the current study, may be better suited for predicting drug bioavailability and passive transport over epithelia as compared to the octanol-water distribution [3][4][5].…”
mentioning
confidence: 99%